2014
DOI: 10.1097/prs.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Patient Selection Optimization following Combined Abdominal Procedures

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…Thus, there is a consensus on higher complication rates after VHR in morbidly obese patients, BMI≥40; however, our analysis indicates that obese patients (BMI≥30) undergoing VHR have an OR of 2.13 (95% CI 1.24 to 3.67, p=0.01) of postoperative complications [8,18]. The mechanisms underlying the increased complication rate in obese patients are likely multifactorial, but hypotheses exist that may explain the predisposition for complications in obese and hypertensive patients [10]. Impaired visualization due to body habitus in addition to defects in tissue structure and healing are likely contributors to postoperative complications after VHRs in obese patients [19].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thus, there is a consensus on higher complication rates after VHR in morbidly obese patients, BMI≥40; however, our analysis indicates that obese patients (BMI≥30) undergoing VHR have an OR of 2.13 (95% CI 1.24 to 3.67, p=0.01) of postoperative complications [8,18]. The mechanisms underlying the increased complication rate in obese patients are likely multifactorial, but hypotheses exist that may explain the predisposition for complications in obese and hypertensive patients [10]. Impaired visualization due to body habitus in addition to defects in tissue structure and healing are likely contributors to postoperative complications after VHRs in obese patients [19].…”
Section: Discussionmentioning
confidence: 60%
“…Certain comorbidities such as obesity, smoking history, and diabetes mellitus have also been associated with increased complications [8,9]. Preexisting hypertension is associated with increased rates of complications in abdominal surgical procedures overall; however, there is a lack of evidence on hypertension as a risk factor in hernia repairs, specifically [10].…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery is a commonly performed highly effective treatment in achieving long-term weight loss and resolution of obesity-related comorbidities. However, in the majority of these patients body contour irregularities and postoperative hernias (in 10–50%) form after open bariatric procedures [15]. Skin redundancy at different body parts observed in more than two-thirds of patients after major weight loss, in some cases with malpositioned adipose tissue, are responsible for hygiene problems, persistent inflammatory changes inside skin folds and both for physical and psychosocial discomfort for the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Given the excellent intraoperative exposure of the abdominal wall during abdominal contouring surgery, concurrent ventral, umbilical, or inguinal hernia repair is also often performed. Despite generally higher risk of complications (seroma formation, wound infection) following simultaneous abdominal wall surgery, most of the authors reported favorable outcomes of abdominoplasty combined with hernia repair [1, 3, 13, 16]. Complex body contouring surgery in postbariatric groups after massive weight loss has been discussed regarding postoperative results and patients’ life quality, however, there are no reports on long-term observations comparing abdominoplasty along with incisional hernia repair (IHR) performed using two separate techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Uma análise de 4925 pacientes submetidos à abdominoplastia com ou sem hernioplastia concomitante evidenciou que os procedimentos combinados apresentavam maiores complicações em relação ao procedimento único. Hipertensão, tabagismo e uso crônico de esteroides foram identificados como preditores de complicações, e o grupo com a cirurgia combinada (abdominoplastia associada à hernioplastia) teve maior taxa de complicações (18,3% versus 9,8%) 4 .…”
Section: Discussionunclassified